PENGARUH PEMBERIAN EKSTRAK BUAH MERAH (Pandanus conoideus) TERHADAP KADAR GLUKOSA DARAH TIKUS PUTIH (Rattus norvegicus) DIABETIK - Rahmi Febriyanti (State Islamic University of Sultan Syarif Kasim Riau, 2011)
This research was conducted to determine the effect of extract of buah merah (Pandanus conoideus) on bloodglucose levels in rats (Rattus norvegicus) diabetic. The samples used were 20 male Wistar rats, aged 2 months and weighed160-180 grams were divided into four groups randomly each of five rats. I as a normal control group were given distilledwater, 1 ml / head / day / orally, group II as control of alloxan, alloxan injected dose of 140 mg / kg bw / ip on day 2, group IIIwere injected with alloxan 140 mg / kg bw / ip on day-to-two, was given a dose of buah merah extract 4 g / kg bw / day /orally day 3 until day 21, group IV injected with alloxan dose of 140 mg / kg bw / ip on days 2 and extract buah merah dose17 g / kg bw / day / orally day 3 until day 21. Blood glucose levels checked for day-to-0, 3, 6, 10, 14, and 22. Blood glucosedata were analyzed statistically by using analysis of variance (ANOVA) of One Way Anova, followed by the Tukey-test andLSD test. The results after 24 hours were given alloxan (day 3) an increase in blood glucose levels significantly (p <0.05) ingroup II, III, and IV compared with group I (control). After treatment with buah merah extract in group III and IV decreasedglucose levels (p <0.05) on day 6 until the last day of the study (day 22).From the research, buah merah extract dose 4 g / kgbw / day / orally and 17 g / kg bw / day / orally can decrease blood glucose levels in diabetic rats (p <0.05).